Clinical Study of Liver Cirrhosis with Special Reference to Thyroid Function: A Cross Sectional Study - Ahsan Javed, Rehab Anjum Dar, Iffat Batool, Bakht Babar, Andeebia Ayub Khan, Rizwan Sadiq, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this study was to assess liver cirrhosis with special reference to thyroid function. Study Design: The study was a cross-sectional one. Setting: Research was conducted at Department of Medicine, Shaikh Zayed Hospital, Lahore from August 2022 to January 2023. Material and Methods: In this study, 115 patients with cirrhosis who were both male and female and between the ages of 20 and 70 were included. These patients underwent thyroid function tests. Each patient provided written informed consent. Results: The average patient's age was 51.78±9.17 years old, and their ages ranged from 35 to 70. The vast majority of patients (n=119, or 55.6%) were between the ages of 53 and 70. Patients included 71 males (61.73% of the total) and 44 females (38.8%). The average duration of illness was 23.78 ±10.05 months, although it may be as little as 8 months. A total of 34 patients (29.56%) were classified as Child Class-B, while 81 patients (70.43%) were classified as Child Class-C. The range of serum TSH was from 3.5 to 5.8 uIU/ml (mean 4.32±0.43 uIU/ml), while the range of serum fT3 was from 1.2 to 2.9 pg/ml (mean 1.87± 0.38 pg/ml). The average serum fT4 concentration was 1.68 pg/ml (standard deviation = 0.47). Practical Implication: Especially in low and middle income countries, there is a lack of consistent data on the impact of cirrhosis on thyroid function and the association of thyroid hormone levels in patients with cirrhosis. In order to better understand the medical picture of cirrhosis of the liver and its relationship to thyroid function, the current investigation was carried out at a tertiary care center. Conclusion: Liver cirrhosis patients had lower mean blood levels of fT3 and fT4. However, the mean serum TSH level was higher in this group of individuals. It was shown to be significantly higher in patients with more advanced liver disease, but not to differ significantly by age, gender, or disease duration. Keywords: Thyroid Function, Liver Cirrhosis, Child-Pugh Classification